Research on multi-objective operation optimization of multi energy integrated service stations based on autonomous collaborative control - Jian Geng; Tao Zheng; Jing Cao; Yufeng Yang; Yulong Jin; Jinzhou Fu (Energy Reports, 2022)
Multi energy integrated service stations have strong comprehensive energy and coupling properties, covering functional units such as substation, multi type energy conversion station, data center, distributed power generation, charging and replacement power station, wireless base station and so on. However, with the continuous improvement of the physical complexity of power grid information, there are still great theoretical and practical difficulties on how to build the operation optimization architecture of energy integrated service station and realize the organic integration of energy flow, data flow and business flow. The typical model forms of various equilibrium equality constraints and inequality constraints between stations and stations are established, and the multi-objective operation optimization model is established and solved. The results show that it improves the level of multi energy conversion, multi energy complementarity, comprehensive energy utilization efficiency, realizes the purpose of collaborative control optimization of multiple energy integrated service stations, and effectively promotes the maximum local consumption of renewable energy.